Visible‐Light‐Induced Palladium‐Catalyzed Dehydrogenative Carbonylation of Amines to Oxalamides. Issue 18 (1st March 2021) - Meyer, Tim; Rabeah, Jabor; Brückner, Angelika; Wu, Xiao‐Feng
Abstract: The palladium‐catalyzed oxidative carbonylation of amines toward the synthesis of oxalamides has been established around 30 years ago and it usually needs the presence of (over)stoichiometric amounts of oxidant. In this work, the first transformation of this type in which the oxidant was replaced by visible light is described. The new approach uses a simple robust Pd complex, which can even be partially recycled. A mechanistic reason is provided and supported by control experiments and EPR studies, showing that Pd I was formed and Pd 0 was the active species. Both nitrogen‐ and the intermediate acyl radical can be detected. Moreover, the formation of hydrogen was confirmed by gas GC. Abstract : The first example on oxidative carbonylation of amines to oxalamides driven by visible light with the release of hydrogen gas has been developed. The new approach uses a simple robust Pd complex, which can even be partially recycled. A mechanistic reason is provided and supported by control experiments and EPR studies, showing that Pd I formed and Pd 0 was the active species. Both nitrogen‐ and the intermediate acyl radical were detected.